Vector competence of the tick Ixodes ricinus for transmission of Bartonella birtlesii. - Caroline Reis; Martine Cote; Danielle Le Rhun; Benoit Lecuelle; Michael L Levin; Muriel Vayssier-Taussat; Sarah I Bonnet (Public Library of Science (PLoS), 2011)
Bartonella spp. are facultative intracellular vector-borne bacteria associated with several emerging diseases in humans and animals all over the world. The potential for involvement of ticks in transmission of Bartonella spp. has been heartily debated for many years. However, most of the data supporting bartonellae transmission by ticks come from molecular and serological epidemiological surveys in humans and animals providing only indirect evidences without a direct proof of tick vector competence for transmission of bartonellae. We used a murine model to assess the vector competence of Ixodes ricinus for Bartonella birtlesii. Larval and nymphal I. ricinus were fed on a B. birtlesii-infected mouse. The nymphs successfully transmitted B. birtlesii to naïve mice as bacteria were recovered from both the mouse blood and liver at seven and 16 days after tick bites. The female adults successfully emitted the bacteria into uninfected blood after three or more days of tick attachment, when fed via membrane feeding system. Histochemical staining showed the presence of bacteria in salivary glands and muscle tissues of partially engorged adult ticks, which had molted from the infected nymphs. These results confirm the vector competence of I. ricinus for B. birtlesii and represent the first in vivo demonstration of a Bartonella sp. transmission by ticks. Consequently, bartonelloses should be now included in the differential diagnosis for patients exposed to tick bites.